Understanding the Walkability Propensity - Marialisa Nigro; Marco Petrelli; Rasa Ušpalytė-Vitkūnienė; Daiva Žilionienė (The Baltic Journal of Road and Bridge Engineering)
Walkability analysis has grown in popularity in recent years: several studies have analysed the public health, economic, environmental, transportation and other benefits of promoting walkability. Different authors in the literature focus on the analysis of walking indicators related to the structure of the road network to explain the walkability of an area. However, extra efforts have to be made to study many other conditions that affect the propensity to walk: not just the shape of the network and the urban topology, but also the security and the attractiveness of the landscape, or specific characteristics of the infrastructure such as the size of the sidewalks, the automobile accommodation values (automobile and motorcycle parking) and the pedestrian route difficulty (slope and over length of the paths, dead-end streets). This paper aims to understand the walkability propensity, investigating explanatory variables related to the concept of the pedestrian path quality at the microscopic level. Several data have been collected in different zones of the Rome City (Italy), utterly dissimilar from the pedestrian point of view. These data have been compared with the real path for pedestrian choices and with other standard walkability measures from literature.